Adsorption, transformation, and colloid-facilitated transport of nano-zero-valent iron in soils. Issue 1 (1st January 2019) - Zhang, Shugang; Li, Xuan; Yang, Yuechao; Li, Yuncong; Chen, Jianqiu; Ding, Fangjun
ABSTRACT: Because of its unique reductive properties, nanoscale zero-valent iron (NZVI) has been widely used in soil and groundwater remediation. It is crucial to understand the fate of NZVI in soils. In this work, a range of laboratory experiments was conducted to examine the adsorption, transformation, and transport of NZVI. The NZVI particles showed relatively strong sorption onto vertic shajiang-aquic cambosols, typic-hapli-udic argosols and typic ochri-aquic cambosols and isotherms can be well described by the Langmuir model. When cultivated in the soils, the NZVI was oxidized within seven days and the particle size also increased with average size reaching around 100 nm at 28 days. Columns were packed with quartz sand, sandy soil and diatomite as saturated porous media to evaluate the role of soil colloids in affecting the transport of NZVI. The results showed that NZVI transport in the columns was strongly affected by medium types, dispersion agent types, and soil colloids. Comparisons of breakthrough curves of different types of dispersed NZVI and corresponding colloid-NZVI revealed that natural soil colloids facilitated NZVI transport in porous media. Findings from this work can provide useful information to better evaluate the applications and impacts of NZVI as an environmental remediation agent.